Technological Integration in Ecological Civilization Education: A Mixed-Methods Exploration in Chinese Tertiary Institutions within the Intelligent Era - Chen Jie; Mohamad Jafre Bin Zainol Abidin (Eximia, 2024)
In the current Intelligent Era, the integration of technology into Ecological Civilization Education (ECE) has become a central consideration in modern pedagogy. This research delves into the relationship between technological advancements and the delivery of ECE in higher education institutions in China. Using a mixed-method approach, insights from 1,500 students were collected through meticulously crafted questionnaires and in-depth interviews. The results indicate a pronounced inclination toward incorporating technology into ECE, with the Problem-Based Learning (PBL) method being particularly effective. Contemporary tools like digital simulations and Augmented and Virtual Reality are emphasized for their educational value. Nonetheless, concerns arose regarding technology’s potential to shift focus away from core ecological principles. In conclusion, this study underscores the importance of a harmonious blend of technology and ECE, aiming to foster enriched learning experiences while upholding the essence of fundamental ecological teachings.